Improving Students’ Learning Outcome in Mathematics with Brainstorming Model - Hotmaida Siregar (RADINKA JAYA UTAMA PUBLISHER, 2023)
This study aims to determine the effectiveness of the Brainstorming model in improving Mathematics learning outcomes in junior high school level. The participants in this study were 26 students in Kelas IX-1 in SMP Negeri 4 Padangsidimpuan. This class action research (CAR) is qualitative study conducted in two cycles. Data collection did by document analysis and class observation technique. The finding then analyzed and reviewed qualitatively based on the theory of the Brainstorming and other relevant theories explained in this study. The results of this study reveals that Brainstorming method can improve students’ Mathematics learning outcomes in Kelas IX-1 in SMP Negeri 4 Padangsidimpuan. Teacher's maximum scaffolding helps students to get involve and motivated. However, other study still needed in a larger scale to obtain better results.